2021
DOI: 10.1161/circulationaha.120.051783
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Empagliflozin on the Clinical Stability of Patients With Heart Failure and a Reduced Ejection Fraction

Abstract: Background: Empagliflozin reduces the risk of cardiovascular death or hospitalization for heart failure in patients with heart failure and a reduced ejection fraction, with or without diabetes, but additional data are needed about the effect of the drug on inpatient and outpatient events that reflect worsening heart failure. Methods: We randomly assigned 3730 patients with class II-IV heart failure with an ejection fraction of ≤40% to double-blind treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
226
1
29

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 313 publications
(270 citation statements)
references
References 35 publications
14
226
1
29
Order By: Relevance
“…Thus, the detailed analyses from two large outcome trials in HFrEF with SGLT2 inhibitors 6 , 7 now substantiate the first crude data already reported in the original publications 4 , 5 as well as in the meta-analysis of DAPA-HF and EMPEROR-Reduced showing that patients treated with an ARNI derive at least the same benefit from additional SGLT2 inhibitor treatment as patients not on an ARNI. 8 …”
supporting
confidence: 67%
See 2 more Smart Citations
“…Thus, the detailed analyses from two large outcome trials in HFrEF with SGLT2 inhibitors 6 , 7 now substantiate the first crude data already reported in the original publications 4 , 5 as well as in the meta-analysis of DAPA-HF and EMPEROR-Reduced showing that patients treated with an ARNI derive at least the same benefit from additional SGLT2 inhibitor treatment as patients not on an ARNI. 8 …”
supporting
confidence: 67%
“…Patients taking a neprilysin inhibitor at baseline, for example, had slightly lower blood pressure, and were more likely to be treated with implantable cardioverter-defibrillator and/or cardiac resynchronization therapy. 7 Side effects were similar in patients taking or not taking an ARNI; symptomatic hypotension non-significantly tended to be more frequent in patients on sacubitril/valsartan.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Several mechanism(s) have been put forward to help explain the benefits of SGLT2 inhibition on heart failure 14,36–39 . The early separation of the curves (within days)—which is also seen for dapagliflozin in DAPA‐HF 40 and for empagliflozin in EMPEROR‐Reduced 30 — may point toward an important haemodynamic effect of SGLT2 inhibition in patients with heart failure. Indeed, recent human physiological studies in heart failure have indicated that SGLT2 inhibition promotes fractional sodium excretion within a few hours of treatment initiation—an effect that is exaggerated in the context of a loop diuretic 41 .…”
Section: Figurementioning
confidence: 99%
“…El estudio EMPEROR-Reduced (5) encontró que el inhibidor del cotransportador sodio -glucosa 2 (iSGLT2): empaglifozina disminuyó el combinado de muerte CV o primera hospitalización por IC en pacientes con fracción de eyección (FEVI) ≤40%, con un número necesario a tratar (NNT) de 19 a 16 meses, y un efecto significativo desde el día 12 de iniciado el medicamento (6) . Asimismo, con un efecto añadido de nefro protección (menor tasa de disminución en la función renal, con ↓ en riesgo relativo [RR] de 50%), hace que los iSGLT2 se posicionen con un beneficio de clase, que anticipa sean un pilar de tratamiento de los pacientes con IC con fracción de eyección reducida (IC-FEr) para la próxima guía de IC de la Sociedad Europea de Cardiología 2021 (Figura 1).…”
Section: Insuficiencia Cardiacaunclassified